Severe structural valve deterioration after TAVR with ACURATE Neo: report of two cases - Schaeffer, Thibault; Koechlin, Luca; Jeger, Raban; Leibundgut, Gregor; Reuthebuch, Oliver (Frontiers in Cardiovascular Medicine, 2023)
Structural valve deterioration (SVD) of transcatheter implanted aortic valve (TAVR) prostheses leading to prosthesis dysfunction is an uncommon but increasingly described complication. Literature is scarce on specific mechanisms and clinical presentation of SVD after TAVR, notably on the self-expanding valve ACURATE Neo. We report on two cases of severe bioprosthetic failure due to leaflet disruption less than five years after ACURATE Neo implantation, which we treated with surgical aortic valve replacement. We further discuss the incidence of SVD after TAVR, the durability of ACURATE NEO, and the modes of failure of biological valve prostheses.